Exploring the Potential of Constructivist Pedagogical Approach in Strengthening Religious Moderation a Systematic Literature Review - Fadlillah, Nilna; Abdullah, Moh.; Kusaeri, Kusaeri (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study aims to outline various previous research findings related to applying the constructivist pedagogy approach in improving moderate attitudes in educational institutions and explore the potential of the constructivist pedagogy approach to internalize the value of religious moderation in Indonesian education. This research uses the Systematic Literature Review method using the Watase Uake tool and the Google Scholar search engine. The data in this study are articles indexed in Q1, Q2, Q3, and Q4. The articles were selected using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) technique. After going through the identification, screening, and eligibility process, 48 articles were included in the inclusion stage and analyzed using the meta-synthesis technique. The results of this study show that i) the findings of previous studies indicate that constructivist pedagogical approaches contribute positively to increasing openness and tolerance towards differences and building more appropriate attitudes in understanding diversity; ii) through constructivist activities, egalitarian teacher-student interactions, and inclusive social activities, students can develop a deeper understanding of the values of religious moderation (such as tawassuth, tawazun, tasamuh, musawah, and shura), appreciate the diversity of beliefs, and build openness to differences, so that constructivist approaches in learning have great potential to improve moderate attitudes in religion, especially in the context of Islamic education. The results of this study can positively contribute to the development of curriculum and religious learning methods oriented towards religious moderation in Indonesia.